2020
DOI: 10.1002/esp.4976
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing southern African silcrete geochemistry: implications for silcrete origin and sourcing of silcrete artefacts

Abstract: A synthesis of the geochemistry of silcretes and their host sediments in the Kalahari Desert and Cape coastal zone, using isocon comparisons, shows that silcretes in the two regions are very different. Kalahari Desert silcretes outcrop along drainage-lines and within pans, and formed by groundwater silicification of near-surface Kalahari Group sands. Silicification was approximately isovolumetric. Few elements were lost; silicon (Si) and potassium (K) were gained as microquartz precipitated in the sediment por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…In the present study, the isocon line was drawn through the Zr value for each sample, as Zr in the hornfels appears to be present mostly as zircon grains, which are very insoluble and extremely resistant to weathering and diagenetic processes (Morton, 1984; Pettijohn, 1941; Thornber, 1992). Many studies of regolith processes have found Zr to be immobile (e.g., Shackley, 2011; Webb & Golding 1998; Webb & Nash, 2020), and it has been considered as such in this study. During hydrothermal alteration, Zr is almost invariably immobile along with Ti (Grant, 1986); the fact that in the present case Ti plots on the isocon defined by Zr supports the immobility of both elements during hornfels weathering (discussed further below).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the isocon line was drawn through the Zr value for each sample, as Zr in the hornfels appears to be present mostly as zircon grains, which are very insoluble and extremely resistant to weathering and diagenetic processes (Morton, 1984; Pettijohn, 1941; Thornber, 1992). Many studies of regolith processes have found Zr to be immobile (e.g., Shackley, 2011; Webb & Golding 1998; Webb & Nash, 2020), and it has been considered as such in this study. During hydrothermal alteration, Zr is almost invariably immobile along with Ti (Grant, 1986); the fact that in the present case Ti plots on the isocon defined by Zr supports the immobility of both elements during hornfels weathering (discussed further below).…”
Section: Methodsmentioning
confidence: 99%
“…One possible development and use of our model would consist in adjusting the value of the key rate parameter, i.e., τ , for each type of duricrusts, namely calcretes, silcretes or other types of hardened layers that are likely to form according to the hydrological model. It is known that different types of duricrusts form in different environments, most likely in an optimum moisture/climatic gradient in time and space (Webb and Nash, 2020;Taylor and Eggleton, 2001;Khalifa et al, 2009;Momo et al, 2020;Mather et al, 2019;Watson, 1988). Using the model, we could then map the tectonic and climatic scenarios under which each type of crust forms and explore potential differences in their long-term preservation.…”
Section: Generalisation To Other Crustsmentioning
confidence: 99%
“…Nash et al, 2013. For example, the large geochemical datasets arising from this work have been used by Webb and Nash (2020) to constrain the environmental controls upon silcrete formation in the Botswana Kalahari (see section X.3.3).…”
Section: X3 Silcretementioning
confidence: 99%
“…For readers seeking general information about silcrete, useful reviews are provided by Milnes and Thiry (1992), Nash and Ullyott (2007), Nash (2011Nash ( , 2012 and, from an archaeological perspective, Thiry and Milnes (2017). Overviews that focus on silcretes in Botswana are limited to early studies such as Goudie (1973) and Summerfield (1982;1983b;1983a) and the more recent syntheses by Nash (2012) and Webb and Nash (2020).…”
Section: X3 Silcretementioning
confidence: 99%
See 1 more Smart Citation